Pengaruh Pemberian Posisi Fowler terhadap Saturasi Oksigen pada Pasien Pasca Operasi Odontektomi di IBS RSUD dr. Tjitrowardojo Purworejo - Muhamad Yusup Halabi; Istiqomah Rosidah; Aisyah Nur Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
Patients who have undergone odontectomy surgery are at risk of respiratory failure due to decreased oxygen saturation. Good handling is needed to overcome this, especially by placing the patient in the 60° Fowler position for 10 minutes, which facilitates breathing because gravity pulls the diaphragm down, increasing lung expansion. The purpose of this study was to determine how giving the 60° Fowler position to post-odontectomy patients affects their oxygen saturation levels. This study used a pre-experimental design using the pre-experiment one group pre-post test methodology. The sampling technique used purposive sampling of 36 respondents with an instrument in the form of an observation sheet. The statistical test used the Wilcoxon Sign Rank test to determine the effect of the fowler position variable on changes in oxygen saturation in post-odontectomy patients. The majority of respondents before being given the 60⁰ fowler position had oxygen saturation in the mild hypoxemia category of 25 respondents (69.4%). After being given the 60⁰ fowler position intervention, all respondents experienced a very significant average increase of 6.3%. The Wilcoxon test results obtained a result of 0.000 (p <0.05). There is a significant effect of giving the 60˚ fowler position on changes in oxygen saturation in post-odontectomy patients at IBS RSUD Dr. Tjitrowardojo Purworejo.